Progressive Macular Hypomelanosis: A Rarely Diagnosed Hypopigmentation in Caucasians - Sven Neynaber; Christina Kirschner; Stefanie Kamann; Gerd Plewig; Michael J. Flaig (Dermatology Research and Practice)
A 35-year-old woman who developed whitish macules on trunk and limbs at 12 years of age and observed a remarkable increase of the hypopigmentated lesions after her pregnancies at ages 29 and 32 years. Because of the highly characteristic clinical aspect and the light- and electron-microscopic histopathologic findings, we diagnosed progressive macular hypomelanosis (PMH). It is a nonscaly disorder with hypopigmented macules mainly on the trunk and is more often seen in young women. In contrast to some authors assuming the presence of Propionibacterium spp. as a matter of principle in PMH, we report a case with no evidence for Propionibacterium spp.